2020
DOI: 10.1111/ppc.12664
|View full text |Cite
|
Sign up to set email alerts
|

Examination of nursing students' anxiety levels related to clinical practice with respect to peer support

Abstract: Purpose: To investigate the relationship between stress and anxiety levels of nursing students at during their first clinical practice.Design and Methods: Designed as a quasi-experimental study with a study group (n = 13) and a control group (n = 13) among nursing students at a university.Findings: Students who practiced in the clinic for the first time experienced stress and anxiety, and their stress levels increased with high levels of state anxiety. The stress and anxiety decreased using peer support of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In a study by Atay and Yilmaz (2011), students reported higher levels of clinical stress with their sense of threat and harm (18). In Tambağ's study, it was reported that the anxiety level of students who went into clinical practice for the first time was high (27). In another it was reported that students experienced moderate anxiety before clinical practice (28).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Atay and Yilmaz (2011), students reported higher levels of clinical stress with their sense of threat and harm (18). In Tambağ's study, it was reported that the anxiety level of students who went into clinical practice for the first time was high (27). In another it was reported that students experienced moderate anxiety before clinical practice (28).…”
Section: Discussionmentioning
confidence: 99%
“…Principal limitations of the investigations were ethics and bias, implications and usefulness, and transferability or generalizability. Only two studies included information on how the authors' own bias was addressed (Tambağ, 2021 ; Wang et al., 2021 ), only four studies fully addressed implications for policy and/or practice (Latif & Nor, 2019 ; Ma et al., 2022 ; Tambağ, 2021 ; Wang et al., 2021 ), and a detailed description of the context or setting in which the study was conducted fully described in only four studies (Alanazi et al., 2023 ; Ma et al., 2022 ; Tambağ, 2021 ; Wang et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Social support was identified in seven studies (Alshahrani et al., 2018 ; Durgun Ozan et al., 2020 ; Fang et al., 2020 ; Lavoie‐Tremblay et al., 2022 ; Onieva‐Zafra et al., 2020 ; Tambağ, 2021 ; Wang et al., 2021 ). Studies identify social support received specifically from family and friends (Alshahrani et al., 2018 ; Fang et al., 2020 ), and also from peers (Tambağ, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, it has been observed that persons with neuroticism tend to experience negative emotions in response to threats, frustration, or loss [ 41 ]. For nursing students, the university environment, together with the associated clinical placements, puts them in complex situations that can create feelings of anxiety, frustration, and loss or that may be perceived as threatening (in areas such as exams, scholarships, and feelings of insecurity in dealing with patients) [ 42 , 43 ]. All of these pressures contribute to burnout in students.…”
Section: Discussionmentioning
confidence: 99%